Irregular Aharonov–Bohm effect for interacting electrons in a ZnO quantum ring. (30th December 2016) - Chakraborty, Tapash; Manaselyan, Aram; Barseghyan, Manuk
Abstract: The electronic states and optical transitions of a ZnO quantum ring containing few interacting electrons in an applied magnetic field are found to be very different from those in a conventional semiconductor system, such as a GaAs ring. The strong Zeeman interaction and the Coulomb interaction of the ZnO system, two important characteristics of the electron system in ZnO, exert a profound influence on the electron states and on the optical properties of the ring. In particular, our results indicate that the Aharonov–Bohm (AB) effect in a ZnO quantum ring strongly depends on the electron number. In fact, for two electrons in the ZnO ring, the AB oscillations become aperiodic, while for three electrons (interacting) the AB oscillations completely disappear. Therefore, unlike in conventional quantum ring topology, here the AB effect (and the resulting persistent current) can be controlled by varying the electron number.